2019
DOI: 10.3390/ijms20225746
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-Induced Hormonal Changes in eds5 and sid2 Mutant Arabidopsis Plants

Abstract: Polyamines are multifaceted compounds which play a role in regulating plant growth and stress tolerance in interactions with plant hormones. The aim of the present study was to reveal how exogenous polyamines influence the synthesis of salicylic acid, with a special emphasis on the effect of salicylic acid deficiency on the polyamine metabolism and polyamine-induced changes in other plant hormone contents. Our hypothesis was that the individual polyamines induced different changes in the polyamine and salicyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 83 publications
3
19
0
Order By: Relevance
“…Importantly, Spm concentrations found to be effective in this work (low µ m range) are significantly lower than the basal polyamine levels in plant cells (Galston and Kaur‐Sawhney, 1995), and much lower than concentrations frequently used in other studies, where typically high µ m /low m m concentrations have been used (Sagor et al ., 2015; Marco et al ., 2019; Tajti et al ., 2019). In our hands, the effective concentration of Spm to induce PIP 2 revealed a clear saturation response at low µ m concentrations (Figure 1) and correlated with the dose‐dependent inhibition of root growth (Figure 6; Zarza et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Spm concentrations found to be effective in this work (low µ m range) are significantly lower than the basal polyamine levels in plant cells (Galston and Kaur‐Sawhney, 1995), and much lower than concentrations frequently used in other studies, where typically high µ m /low m m concentrations have been used (Sagor et al ., 2015; Marco et al ., 2019; Tajti et al ., 2019). In our hands, the effective concentration of Spm to induce PIP 2 revealed a clear saturation response at low µ m concentrations (Figure 1) and correlated with the dose‐dependent inhibition of root growth (Figure 6; Zarza et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These papers cover a wide range of aspects of SA-related mechanisms. They include a "classical" demonstration of the importance of SA in biotic stress [23] and the importance of the use of various mutants related to SA signalling [24,25], as well as focus on the crosstalk with other stress-related compounds [25,26]. There are also works investigating the effects of environmental factors on the SA-related signalling [26,27], and on the role of different SA analogue compounds [28].…”
Section: What Are the New Directions?mentioning
confidence: 99%
“…However, their signalling role has only become apparent in recent years [29]. Tajti and co-workers recently demonstrated a possible crosstalk between the SA and polyamine signalling pathways [25]. They showed that the SA-deficient Arabidopsis mutant, sid2 plants, could be characterised with a different polyamine metabolism.…”
Section: What Are the New Directions?mentioning
confidence: 99%
“…Bioinformatics studies revealing the correlation coefficient and clustering analyses might be of interest and provide a comprehensive understanding about the interaction between PAs and genes responsible for SA biosynthesis pathway. The effect of individual PAs on SA biosynthesis and on PA metabolism and vice versa has been previously studied in Arabidopsis plants by exogenous application of PAs or SA using SA mutants (Tajti et al, 2019). Synthesis of polyamine and its catabolism beside the pronounced changes in SA synthesis was upregulated by polyamines treatments in vitro, especially after SPD or SPM (Tajti et al, 2019).…”
Section: Dissection Of Gene Expression Alteration Of Sa Biosynthetic mentioning
confidence: 99%
“…The effect of individual PAs on SA biosynthesis and on PA metabolism and vice versa has been previously studied in Arabidopsis plants by exogenous application of PAs or SA using SA mutants (Tajti et al, 2019). Synthesis of polyamine and its catabolism beside the pronounced changes in SA synthesis was upregulated by polyamines treatments in vitro, especially after SPD or SPM (Tajti et al, 2019). Each PA was found to have a distinct role.…”
Section: Dissection Of Gene Expression Alteration Of Sa Biosynthetic mentioning
confidence: 99%